2014
DOI: 10.7717/peerj.240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lodgepole and jack pine resin chemistry: implications for range expansion by the mountain pine beetle,Dendroctonus ponderosae(Coleoptera: Curculionidae)

Abstract: The mountain pine beetle, Dendroctonus ponderosae, is a significant pest of lodgepole pine in British Columbia (BC), where it has recently reached an unprecedented outbreak level. Although it is native to western North America, the beetle can now be viewed as a native invasive because for the first time in recorded history it has begun to reproduce in native jack pine stands within the North American boreal forest. The ability of jack pine trees to defend themselves against mass attack and their suitability fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 51 publications
4
45
2
Order By: Relevance
“…In this, and many other studies, α-pinene is the most abundant monoterpene in jack pine phloem, but its enantiomeric composition has rarely been measured. Our results show that jack pine phloem contains only half the amount of (−)-α-pinene per unit of phloem tissue compared to lodgepole pine, which is in accordance with the findings of Clark et al (2014). Nonetheless, in laboratory experiments, MPB females emit twice the amount of (−)-trans-verbenol when tunneling in jack pine bolts compared to lodgepole pine (Erbilgin et al, 2014).…”
Section: Discussion Chemical Profiles Of Stem Volatiles Needle and supporting
confidence: 90%
“…In this, and many other studies, α-pinene is the most abundant monoterpene in jack pine phloem, but its enantiomeric composition has rarely been measured. Our results show that jack pine phloem contains only half the amount of (−)-α-pinene per unit of phloem tissue compared to lodgepole pine, which is in accordance with the findings of Clark et al (2014). Nonetheless, in laboratory experiments, MPB females emit twice the amount of (−)-trans-verbenol when tunneling in jack pine bolts compared to lodgepole pine (Erbilgin et al, 2014).…”
Section: Discussion Chemical Profiles Of Stem Volatiles Needle and supporting
confidence: 90%
“…Further, the seedlings used in this study appeared to be predominantly the (+) enantiomer of (1-pinene, rather than the (-) form. This is in contrast to the results of Pureswaran et al (2004), who found that the (-) enantiomer was more abundant in both the bole woody tissue (bark, phloem and sapwood) and foliage of mature trees, and the results of Clark et al (2014) who found only the (-) enantiomer and none of the (+) enantiomer in the phloem tissue of mature trees. Possibly the differences observed between this study and previous work, in these final two terpenes, could be due to using seedlings instead of mature trees or using branches instead of woody tissue from the bole of the tree, as previous studies have suggested that monoterpene compositions can vary between different tissues within the same tree (Pureswaran and Borden 2004 and references within).…”
Section: Chirality O F Terpenescontrasting
confidence: 99%
“…These results are similar to those of Pureswaran et al (2004), who found similar trends of camphene and sabinene, and to those of Clark et al (2014) who found similar trends for a-pinene in lodgepole pine woody tissue. In addition, the (-) enantiomer of a-pinene is the form of the molecule that is converted to the biologically active enantiomer of the pheromone (-) trans-verbenol by MPB females (Borden et al 1987).…”
Section: Chirality O F Terpenessupporting
confidence: 90%
See 1 more Smart Citation
“…However, lack of knowledge regarding altered trophic interactions in novel habitats precluded the capacity to predict the rate of spread and subsequent impacts of the invading population. This point is particularly relevant since new evidence suggests that the defensive response (Clark et al 2010(Clark et al , 2014, the ability of beetles to aggregate (Burke and Carroll 2016), and the ultimate productivity of the mountain pine beetle (Cudmore et al 2010), in putatively "evolutionarily naïve" trees may be very different from expectations derived from the beetle's historic habitat.…”
Section: Dendroctonus Simplexmentioning
confidence: 99%